Konfigurasi Jaringan Komputer Menggunakan Mikrotik - Imam Solikin; Septa Hardini (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2024)
This community service is carried out by students of the AS-SHIDDIQIYAH Vocational High School (SMK) located at Jalan Lintas Timur, Lempuing Jaya District, Ogan Komering Ilir Regency, South Sumatra. This community service takes the form of training in network configuration using Mikrotik. The network life cycle model with the PPDIOO concept is, Prepare, Plan, Design, Implement, Operate and Optimize. This activity takes the form of training on MikroTik configuration as a router. This activity aims to provide participants with an understanding of the basic capabilities of computer networks and the use of MikroTik as a router. The benefit of Mikrotik Router training for As-Shiddiqiah Vocational School students is that they can understand the concept of computer networks on a small, medium or large scale. This allows them to manage and monitor the network well.